(3GdZQQ GdHgjI aj TQM GdHgLI GdhQOjIs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3eMeO Hf eMeO Hf CMeO Hf MSjf Hf MSf GdSNGhi GdTGaYi s)
(3ChdgG (B:s
(3HGH GdLQGM LeY LQGMI s
(3BNQgG (B:s
(3Je GdTQM HMeO Gddg hefg hGdUdGI hGdSdGe Ydi fHjg eMeO hBdg hUMHg GdWjHjf GdWGgQjf hGddg CYde s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdcJGH GdeTQhM(B: (3GdHgLI GdhQOjI ai fXe GdMGhi GdUZjQ dRjf GdOjf YeQ Hf eXaQ GdhQOi GdTGaYi J (B749s
(3GdfSNI HgG MhGTs
(3QGLY LRA BNQ ef GdfSNI (B-(3heYdheGJ GdfSN(B- (3aj fSNI(B: 89/1 (3chjJs
(3aQZ efg eUfag SfI (B867 (3g` ceG ai BNQg s
(3cJH GdfXe HGdeOGO GdCMeQ s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdTGaYjs